SERTIFIKASI : UPAYA MEMANTAPKAN PROFESIONALISME AKUNTAN - Murtanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2002)
Good Corporate Governance (GCG) practice can produce a quality. In implementing GCG accounting profession should response sitively to the changing environment, social needs, and quality demand. Accounting fession should provide a quality service with consistently comply with standards, ethi I principle% and code of ethics. The paper argues that one of strategy to maintain qu ity of accounting profes-sion is to apply a certification process.Keywords: Good corporate governance, Accounting profpssion, Quality service, Certification.